Contribuições para uma aprendizagem significativa de alunos da educação de jovens e adultos - Castro, Inaíria dos Santos (2023)
Youth and adult education is aimed at many people who, often, for socio-cultural and political reasons, did not have access or continuity in their studies. This public is marked by prejudices rooted for years by society, and they are evidenced in inconsistent practices, which generate little participation in the proposed activities and even school dropout. It is known that education should value the prior knowledge of these students, respecting their real needs and inserting activities that arouse attention and guarantee meaningful learning. Organizing teaching-learning situations and using resources and strategies that motivate the interest of this public has been a very opportune strategy, but it is not a very simple task for teachers. In this sense, research work intends to know in: How to contribute with meaningful activities for EJA students to actively participate in the process as protagonists of their teaching-learning? Thus, it has the objective of proposing innovative and meaningful practices for the teaching of natural sciences, through a pedagogical workshop so that the student is active in the process of building knowledge, making use of active methodologies. The research has a qualitative approach, with a study of literature, semi-structured interviews and workshops with organized moments of didactic sequence. We know that the process of change is something that can take years, but it is extremely necessary. We hope to contribute to breaking with the practice of passive teaching, which disregards popular knowledge and the life experiences of people who did not have access to education and, above all, contribute to the EJA student being the protagonist of their knowledge and their knowledge, to provide opportunities for more meaningful learning. Keywords.